Analisis Kesulitan Siswa Dalam Menyelesaikan Soal Operasi Bentuk Aljabar Pada Siswa Kelas VIId SMP Al-Islam Kartasura - KARUNIAWATI, DITA, Rita Pramujiyanti Khotimah, M.Sc (2016)
The aim of this study is to describe the difficulties experienced by students in solving the algebra operations and analyze the factors. This type of research is qualitative descriptive. Subjects in this study were students VIID SMP Al Islam Kartasura in odd semester of the 2015/2016 academic year. Data collection methods used observation, interview, and documentation. Mechanical analysis of data through data reduction, data presentation, and conclusion. The study states (1) difficulty transferring knowledge relating the concept of arithmetic operations algebra, include: difficulties in the concept of multiplication of the tribe with two parts, two parts by the two tribes, and reappointment, and the concept of fractional algebraic form in finding the Least Common Multiple (LCM) or fractional algebraic worth. (2) Difficulties in mathematical language skills that student difficulties in solving algebraic form the story and understand the purpose of the algebra problem. (3) Difficulties in calculating the algebra problem, namely the operations of addition, subtraction, multiplication, and division of integers algebraic form, and calculate the fractional arithmetic operation algebraic form. The factors that cause students to experience difficulties include: the lack of interest of the students, student learning is likely to memorize the material so that there is no clear concept, confusion in the concept of work, work procedures are complicated and lengthy, students are lazy to read text matter, less rigor student while working, less careful in understanding every word on a matter, students rarely do the exercises, the students do not understand the material prerequisites of the integers, lack of motivation to learn, the classroom atmosphere is uncomfortable and monotonous learning strategies.